Studi Komponen Gas Hidrokarbon Batubara Menggunakan Metode Pirolisis Gas Kromatografi - Mulyono Dwiantoro; Sundek Hariyadi (Universitas Muslim Indonesia, 2019)
This recent research was conducted to investigate the characteristics of lignite from organic geochemistry side using pyrolysis method of gas chromatography. Thi aim of the study is to analyze three important things concluding the generated hydrocarbon gases, calculate the gas volume, and investigate its environmental setting. The gas product is called pyrolisat which generated during processing of pyrolysis that shown as chromatogram graph on computer screen concluding group of short carbon- chain (C1-4), medium carbon-chain (C5-14), and long carbon-chain (C15). The research result revealed that short carbon-chain has dominant percentage (81,9%) than medium carbon chain (9,5%) or long carbon chain (8,6%). This condition indicates that coal sample consisted of various organic matter particularly methane which derived from land plants. Based on these research results, it can be conclude that organic matters were originally from terrestrial environmental setting.